Ethical issues and the role of the ethics committees during COVID-19 research in pandemic era: a focus on an Italian ethics committee - Tattoli, Lucia; Abenante, Barbara; Cavallo Perin, Paolo; Maddalena, Marcello; Lupariello, Francesco (Frontiers in Public Health, 2025)
Independent Research Ethics Committees (RECs) are responsible for protecting the rights and safety of participants involved in research studies. They also promote the values of research ethics and ensure the quality of clinical studies. In emergencies, we expect a significant increase in research activities but it is crucial to maintain both the quality of studies and respect for participants’ rights. At the onset of the SARS-CoV-2 pandemic, the World Health Organization recommended an “expedited” approach to REC approvals. This was intended to streamline and optimize review procedures to prevent delays in research that is critical for responding to the global emergency. The authors evaluated the activity of the Inter-company Ethics Committee (IEC) of Turin, Italy, from January 2020 to December 2022 comparing COVID-19-related protocols with those that were not related to COVID-19. Statistical analyses were applied to find if there were statistically significant differences in variables’ distributions between the two groups of studies. The characteristics of the protocols (total 1,667), including study design, funding, and enrollment of minors, were analyzed. Statistical differences were found for three variables: study type, financial support, and distribution of revised protocols by applicants’ medical specialties. The findings underscore the need for careful attention to ethical principles during emergencies, especially given the large number of projects reviewed by the EC. Various challenges were faced, including the demand for expedited approval of proposed studies, the necessity of recognizing the social value of COVID-19 studies while ensuring proper planning and scientific validity, the need to review studies unrelated to COVID-19, and the obligation to protect the dignity and rights of research participants. It is essential to ensure that the standards for ethical review remain uncompromised.